Biology activity cards for design thinking effects on students' creative thinking and self-directedness - Custodio, Hazel Elaine O. (College of Education, University of the Philippines Diliman, 2019)
The main purpose of this study was to investigate the effects of the Biology Activity Cards for Design Thinking on senior high school students' creative thinking skills and self-directedness. This study utilized quasi-experimental two-group pretest-posttest design on two sections of General Academic Strand (GAS) students in a public high school in Taguig City. One class was exposed to Biology Design Thinking (BDT) instruction while the other class was exposed to conventional instruction (Non-BDT). Both sections were taught by the teacher-researcher during the second quarter of the first semester of School Year 2018-2019. The Creative Thinking Skills test for Life Science used in this study was developed by the researcher, validated by experts, and pilot tested in another section of General Academic Strand students of the same school while The Personal Responsibility Orientation to Self-Direction in Learning Scale (PRO SDLS) by Stockdale and Brockett (2011) was used in this study to measure self-directedness. Data were analyzed using t-test for independent samples, t-test for paired samples, Cohen's d, and linear regression. Based on the findings of the study, it was concluded that Biology Activity Cards for Design Thinking improve creative thinking skills and enhance self-directedness. Moreover, creative thinking skill is a significant positive predictor of self-directedness. Therefore, it is recommended that teachers used BDT approach in teaching Life Science and that school administration provide teacher trainings and seminar-workshops and procure equipment in support of the BDT approach. In addition, future researchers should examine the effects of the BDT approach on other variables in the teaching of Life Science.